THE INFLUENCE OF SOCIAL DISTANCE IN THE USE OF REQUEST STRATEGIES IN THE PROPOSAL MOVIE - Veronica Noviyanti Loanata, Flora Debora Floris (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2011)
Request is a face-threatening act (FTA) that requires the ability of the speaker not only in the language itself, but also in applying the language used in its context. One of the social dimensions, named social distance, proposed by Holmes (2001), is found to be given its influence in the use of request. In this study, the writers wanted to know about request strategies spoken by Margaret Tate (a leader) to Andrew Paxton (her assistant) before and after their contract marriage, as seen in The Proposal movie. The writer used qualitative approach supported by quantitative data. The findings of this research show that in general, there are some similarities and differences of the use of request strategies before as well as after the contract marriage. In general, it can be assumed that Margaret's higher social status is giving more influences to the requests spoken to Andrew rather than the social distance itself.Keywords: Request, Request Strategies, Social Distance